Eksperimen Pembelajaran Matematika Melalui Strategi Grup Investigation dan Tipe Two Stay Two Stray (TS-TS) Terhadap Hasil Belajar Siswa Ditinjau dari Motivasi Belajar Siswa Kelas VII SMP Negeri 2 Gemolong Tahun Ajaran 2016/2017 - Wijayanti, Eky Dwi, Dr. Sumardi, M.Si (2017)
This study aims to: (1) examine the effect of learning strategies and the type of investigation group two stay two stray towards mathematics learning outcomes; (2) examined the effect of learning motivation towards mathematics learning outcomes; (3) testing the interaction between learning strategy investigation group and type two stay two stray learning motivation toward mathematics learning outcomes. The research was conducted on the students of class VII Semester Academic Year 2016/2017 Junior High School 2 Gemolong the population of all seventh grade students of numbers 240. This study includes quantitative research with quasi-experimental research design (quasi-experimental research). Classes that the sample in this study were taken with cluster random sampling method. Methods of data collection using the test, questionnaire, and documentation. Data were analyzed using analysis of variance of two lines with different cells. The results of the data analysis with a significance level of 5% was obtained: (1) There is an effect of learning strategies group investigation and type two stay two stray towards learning outcomes of mathematics, (2) There is an effect level of motivation to learn the results of students' mathematics learning, (3) There is no interaction between learning strategy investigation group and type two stay two stray terms of learning motivation towards mathematics learning outcomes. Keywords: investigation group, two stay two stray, motivation to learn, learning outcomes mathematics